Pedagogical Content Knowledge of Science in the Teacher Education Sector: A Developmental and Research Project - Sarangapani, Padma M.; Ramchand, Mythili (INDIAN EDUCATIONAL REVIEW, 2019)
This study attempted to involve teacher educators and student teachers in participatory planning and development of modular curriculum and resources in science and examined its effect on participants’ pedagogical content knowledge. The study had two components: development of a curriculum module and associated resources, and the development of pedagogical content knowledge among the participants (student teachers).